Guidelines of the Association of Anesthesiologists-Intensivists, the Interregional Non-Governmental Organization Alliance of Clinical Chemotherapists and Microbiologists, the Interregional Association for Clinical Microbiology and Antimicrobial Chemotherapy (IACMAC), and NGO Russian Sepsis Forum "Diagnostics and antimicrobial therapy of the infections caused by multiresistant microorganisms" (update 2022) - V. B. Beloborodov; O. V. Goloschapov; V. G. Gusarov; А. V. Dekhnich; M. N. Zamyatin; N. A. Zubareva; S. K. Zyryanov; D. A. Kamyshova; N. N. Klimko; R. S. Kozlov; V. V. Kulabukhov; M. A. Petrushin; et al. (Вестник анестезиологии и реаниматологии)
Strains of microorganisms characterized by resistance to antimicrobial drugs used in medical organizations continue to spread In most regions of the world including Russia. It is clear that it affects both the effectiveness of antimicrobial therapy and tactics and strategy of its use not only in adults patients but also in children. The pandemic of coronavirus infection, in addition, highlighted the growing problems in treatment of invasive mycoses, the dose adjustment of antibiotics during sorption and dialysis therapy methods. These circumstances made it necessary to make adjustments to Guidelines on Diagnostics and Antimicrobial Therapy of Infections Caused by Multiresistant Strains of Microorganisms, which were prepared by a group of leading Russian experts in 2020 [1]. The submitted version of the recommendations was approved on 25.03.2022 at a joint meeting of the working group with representatives of public organizations: Association of Anesthesiologists-Intensivists, the Interregional Non-Governmental Organization Alliance of Clinical Chemotherapists and Microbiologists, the Interregional Association for Clinical Microbiology and Antimicrobial Chemotherapy (IACMAC), and NGO Russian Sepsis Forum. These recommendations reflect an interdisciplinary consensus opinion on approaches to the diagnosis and antimicrobial therapy of infections caused by multiresistant microorganisms. They are based on data from publications obtained from randomized trials as well as based on international clinical guidelines with a high degree of evidence.It is rational to use the Guidelines for determining the tactics of empirical and etiotropic therapy of the most severe infections.